Bridging the digital divide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Bridging the digital divide, Mobile News, Alcatel, 2001 ICTs are more than ever at the heart of our cultural, social and economic evolution. Innovative solutions are being implemented everyday to meet the urgent needs of emerging countries.